When delivery comes to town: The effect of digital distribution platform emergence on industry structure and competition - Raj, Manav; Eggers, J. P. (Strategic Management Journal, 2026)
Research Summary We explore how the emergence of digital distribution platforms (DDPs), platforms that facilitate transactions between consumers and incumbents, affects industry structure and competition. Studying the effect of delivery platforms on restaurants in the United States from 2012 to 2018, we show that DDP emergence increases exit and concentration and reduces business dynamism. We provide speculative evidence that these changes are driven by both an increase in inter‐firm competition as well as increased margin pressure from the platform. We show that strategic positioning shapes how establishments experience such changes to competition and that DDP emergence can cause a revaluation of resources within an establishment's business model. This research documents how technology‐enabled intermediaries can disrupt an industry by altering the basis of competition. Managerial Abstract The emergence of platforms like Grubhub or Instacart that connect consumers to existing incumbent establishments can alter industry structure and within‐industry competition. We study the effect of delivery platforms on restaurants in the United States and show that the emergence of such platforms has increased exit and concentration within the restaurant industry. We present suggestive evidence that these changes are driven by intensified inter‐firm competition and increased margin pressure from the platforms. We then explore which restaurants are better able to weather the emergence of delivery platforms, showing that establishments' strategic positioning and prior investments shape the extent to which delivery platform penetration is beneficial versus detrimental. Through this research, we document how digital distribution platforms can reshape competition within an industry.